Herding behavior and financial market price behavior under the COVID-19 pandemic: implications for the Amman Stock Exchange - Raneem Ghazi Aldeki (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2022)
Purpose — This study investigates herding behavior and the link between herding behavior with the liquidity and volatility of financial markets amid the COVID-19 pandemic.Research method —This study employed the Cross-Sectional Absolute Deviation (CSAD) approach technique for each of the previous and COVID-19 phases, as well as for the complete sample period. The sample includes 172 securities that have been traded in the Amman Stock Exchange from January 2006 to February 2022. The full sample data was separated into three subsamples: 1) the whole period from January 1, 2006, to February 28, 2022; 2) prior the COVID-19 outbreak from January 1, 2006 to February 28, 2020; and 3) during the COVID-19 outbreak from March 1, 2020, to February 28, 2022.Result — The results for the whole sample period show that herding behavior may be detected in the Amman Stock Exchange during down-market intervals, and the result does not change before or during the COVID-19. Furthermore, both down liquidity and down volatility periods exhibit contrary herding behavior. The study found that financial market price behavior is an important factor that may contribute to herding behavior, which occurs when volatility increases and liquidity decreases in the Amman Stock Exchange, and the result does not change prior to the COVID-19 period. While liquidity has a negative and large influence throughout the COVID-19 period, herding tendency does not increase when volatility changes.Recommendation —This study suggested traders to plan their purchasing and selling strategies of financial market instruments in various scenarios amid the COVID-19 pandemic.